The Influence of Rigorous Mathematical Thinking (RMT) Learning Pathway to Junior High School Students’Conceptual Understanding - Nyorid Ardisen Letuna; Destri Natalia; Adersi Amenita da Resureicao (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
The purpose of this study is to determine whether there is a significant influence of the Rigorous Mathematical Thinking (RMT) learning approach to the conceptual understanding of students of SMP Negeri 5 Kupang grade VIII on the concept of the Two Variable Linear Equation System. This is motivated by the difficulty of students in understanding the subject matter because it is considered difficult so that the resulting understanding of students' mathematical concepts is low. This type of research is quasi experimental research (quasi experiment). The research design used was a pretest-posttest non-equivalent control group design. The population in this study were all eighth grade students of SMP Negeri 5 Kupang, selecting samples using a purposive sampling technique. Retrieval of data using the instrument test item description and observation sheet. Samples are given a pre-test, the results are to test homogeneity. From the results, both have homogeneous variance. After the treatment of both samples were given a post-test, the results are to test the research hypothesis. Based on the prerequisite test, the sample is normally distributed and the variance is homogeneous. Based on the initial ability test, there was no difference in the average pre-test values of the two samples. The results of the study by using a hypothesis test that is a two-way ANOVA test showed a significance value of 0.784> 0.05 so it can be concluded that there was no difference in students' conceptual understanding based on the sex of students of SMP N 5 Kupang.